Relationships between the ABO blood group SNP rs505922 and breast cancer phenotypes: a genotype-phenotype correlation study - Rummel Seth; Shriver Craig D; Ellsworth Rachel E (BMC, 2012)
Abstract Background To date, evaluation of the association of the ABO blood group and breast cancer has yielded mixed results. SNP rs505922, located within the first intron of the ABO gene, has been associated with the adenocarcinoma subtype of pancreatic cancer. To evaluate the association between genetic variation in the ABO blood group and risk of breast cancer, rs505922 was genotyped in 629 Caucasian women with invasive breast cancer, representing a variety of clinical and pathological tumor types. Methods Genomic DNA was isolated from blood. TaqMan SNP assay C_2253769_10 was used to determine genotypes for each patient at rs505922. Statistical analysis was performed using chi-square analysis using a P-value <0.05 to define significance. Results Genotypes were generated for 100% of the 629 patients in this study. Allele and genotype frequencies did not vary significantly for age at diagnosis, tumor stage, size or grade, hormone, HER2 or lymph node status, intrinsic subtype, tumor type or patient outcome. Conclusions Allele frequencies for rs505922 did not differ between women with breast cancer and published HapMap frequencies from women of European descent. Further stratification into different tumor phenotypes also failed to reveal an association between rs505922 and any clinical characteristics. Together, these data suggest that the minor allele of rs505922 and the resulting non-O blood types are not associated with increased risk or less favorable tumor characteristics or prognosis in breast cancer.